STUDI TENTANG PENGGUNAAN BAHAN AJAR MATA PELAJARAN EKONOMI MATERI AKUNTANSI PADA KELAS XI IPS SMA NEGERI 1 KOTA MOJOKERTO - NAHDIYATUR ROSIDAH (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This study purpose to determine the types of teaching materials in SMA Negeri 1 Mojokerto City and the reasons teachers choose the teaching materials, determine the feasibility of teaching materials, and study the response of students to the instructional materials used. This study is a descriptive research with quantitative approach. The results showed that the materials used in SMA Negeri 1 Mojokerto City is LKS